Production and Utilization of Insulin from Stevia Leave (Rebaudiana Bertoni) for the Treatment of Diabetes Mellitus - Abubakar, Muhammad Abbagoni; Gutti, Babagana; Abubakar, Abdulhalim Musa; Ali, Amina Mohamed; Sabo, Muhammad Jamil Umar (PT. Riset Press International, 2023)
Stevia (Rebaudiana bertoni) leave, is an ancient perennial shrub mostly found in South America in countries like Paraguay and Brazil. It contains a low-calorie sweetener, which is about 300 times sweeter than sucrose. Diabetes mellitus is among the common metabolic disorders affecting about 2.8% of the world’s population and is reported to reach 5.4% by the year 2025. In this work, insulin was successfully extracted from Rebaudiana bertoni to serve as an alternative to bovine insulin extracted from animals which is devoid of the risk of transferring infectious diseases from the animals to the diabetic patient as is the case with convectional animal-based insulin. Gas Chromatography-Mass Spectroscopy (GC-MS) and Fourier Transform InfraRed (FTIR) analysis were used to analyze and determine the functional groups available in the isolated compound and the results shows that it has retention time of 14.11 min; abundance/peak area (% PA) of 86.613 %; mass number (m/z) of 413 g/mol; molecular peak ion of 149; fragmentation patterns of 7; and C20H29BrO4 as molecular formula and phthalic acid, 8-bromoctyl butyl ester as IUPAC name. The insulin was tested on three groups of rats (Rattus norvegicus) whereby the glucose level was monitored, and the result shows that the extracted insulin was found to be effective in addition to having antidiabetic effect.